Urban Density: assessment of the built stock and its potential - Corrêa, Lina; Carriello , Felix; Carvalho , Rubens M. R. (National Journal of City Management, 2026)
Objective – Analysis of Urban Density, assessing the capacity to meet housing needs in urbanized areas, without expansion, for the preservation of natural environments. Methodology – Evaluation of various measures of Urban Density, mapping population data (IBGE, 2010) and existing built areas (Data Rio/IPP/2013), over the urbanized area of Rio de Janeiro (IBGE, 2015). Based on this analysis, densification projections were made. Originality/Relevance – Discussions about intensifying the use of urbanized areas, aiming to reduce urban expansion and greenhouse gas emissions (GHG), have gained momentum with the urgency of the climate crisis. The relevance of this article lies in the development of a methodology for Density assessment, unfolding into densification projections, which are rarely employed in scientific research. Results – Densification projections resulted in a potential for allocating additional 300,000 housing units, approximately 50% of the total needs and future demands for housing in the city, in an area corresponding to 5% of its territory; demonstrating that urbanized environments can accommodate demographic increases, contributing to the reduction of urban expansion. Theoretical/Methodological Contributions – The exploration of possible scenarios, resulting from the density projection method, has an important contribution to Urban Planning strategies to combat the causes of climate change. Social and Environmental Contributions – Knowledge about the urban territory, through the analysis of Density and densification projections, can indicate pathways for urban management, with Planning tools that guide the meeting of housing needs in existing spaces, with greater social equality and environmental preservation.